2009
DOI: 10.1111/j.1438-8677.2009.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 on grain yield and quality of wheat: results from a 3‐year free‐air CO2 enrichment experiment

Abstract: Spring wheat (Triticum aestivum L. cv. TRISO) was grown for three consecutive seasons in a free‐air carbon dioxide (CO2) enrichment (FACE) field experiment in order to examine the effects on crop yield and grain quality. CO2 enrichment promoted aboveground biomass (+11.8%) and grain yield (+10.4%). However, adverse effects were predominantly observed on wholegrain quality characteristics. Although the thousand‐grain weight remained unchanged, size distribution was significantly shifted towards smaller grains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
180
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(233 citation statements)
references
References 29 publications
25
180
4
4
Order By: Relevance
“…Apart from this, elevated CO 2 (eCO 2 ) is also known to directly alter grain yield and quality of important agricultural crops such as wheat [2] [3]. Many studies have reported altered protein content and nutritional value of wheat seed as affected by eCO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from this, elevated CO 2 (eCO 2 ) is also known to directly alter grain yield and quality of important agricultural crops such as wheat [2] [3]. Many studies have reported altered protein content and nutritional value of wheat seed as affected by eCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported altered protein content and nutritional value of wheat seed as affected by eCO 2 . Some demonstrated decrease of total grain protein concentration by 3.5% -14.3% [4] [5] while others reported altered protein composition [2] [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a number of countries, its influence on the formation of technological properties of flour and dough is studied [25,[43][44][45]. In some studies, besides properties, the changes in the grain proteome under the action of elevated CO 2 concentration have been assessed [45,46].…”
Section: Dynamicsmentioning
confidence: 99%